Mobile and wearable technologies in healthcare for the ageing population. (July 2018) - Malwade, Shwetambara; Abdul, Shabbir Syed; Uddin, Mohy; Nursetyo, Aldilas Achmad; Fernandez-Luque, Luis; Zhu, Xinxin (Katie); Cilliers, Liezel; Wong, Chun-Por; Bamidis, Panagiotis; Li, Yu-Chuan (Jack)
Abstract: The 16th World Congress on Medical and Health Informatics (MedInfo 2017) was held August 21–25, 2017, in Hangzhou, China. It provided a valuable platform for sharing the latest medical and health informatics research and related applications to the scientists, medical practitioners, entrepreneurs, and educators as well as students. During this event, on August 23, 2017, an important related topic was presented in a panel discussion entitled "Wearable technologies: Advancing the healthcare in ageing population" by panelists Shabbir Syed-Abdul, Panagiotis Bamidis, Chun-Por Wong, and Xinxin Zhu. Recent advances in health technologies, focusing on the aging population, their benefits and challenges were discussed, and these topics are summarized in this paper. The need for technology to improve of the life of older population, influential and beneficial technologies, for delivering these technologies to patients are described in this paper.